Quantitative Value Chain Analysis : An Application to Malawi - Tchale, Hardwick; Keyser, John (2012)
The Government of Malawi has since 2005 been pursuing a growth strategy mainly based on increasing the volume of agricultural exports. This entails that Malawi should endeavor to improve the competitiveness of its agricultural commodities so as to gain an increasing share of the regional and international markets. This paper analyzes the competitiveness of the country's key agricultural commodities -- tobacco, maize, cotton, and rice -- using prices that prevailed in the 2007/08 agricultural season. The paper employs a quantitative value chain methodology to assess the country's prospects for competitiveness and suggest weak links along the value chain that require attention in order to improve trade competitiveness. The results indicate that Malawi has some competitive advantage in the production and exportation of tobacco and cotton, and that this mostly derives from its low labor cost advantage. However, the results indicate that based on 2007/08 prices and costs, Malawi does not have competitive edge in maize and rice production for export. As such, Malawi would better pursue an import substitution strategy in these cereals, and perhaps only aim at the export market when regional market opportunities arise. Key factors that underpin Malawi's narrow competitiveness include the high cost of inorganic fertilizer and other inputs, low productivity, and the higher trader margins and intermediation costs along the value chains. Furthermore, farm gate prices in Malawi are higher than in other countries, and this undercuts its trade competitiveness.